Estimation of the applied doses in irradiated anchovy and bluefish for shelf-life extension using image analysis in combination with DNA comet assay - Nurcan Cetinkaya; Erhan Ic; Yakup Erel; Demet Ercin; Sumer Ozvatan; Nizamettin Yazici (Food Materials Research, 2023)
The objective of the present study was to estimate applied doses of irradiated anchovy (1.83−4.22 kGy) and bluefish (1.98−5.40 kGy) for shelf-life extension by using image analysis in combination with comet assay for trading irradiated fish, especially for public health concerns. Comet assay was carried out considering the EN 13784 protocol. Observed comets were evaluated and recorded by the use of image analysis software (BS 200 ProP). Comets with long tails were observed in the irradiated anchovy and bluefish tissues. However, limited numbers of comets in intact cells were determined in the unirradiated samples. The obtained results clearly indicated that head diameter, head DNA, tail DNA, tail length, and tail moment parameters showed very good correlation (R2 = 0.82 and 0.77 for anchovy and bluefish respectively) with the applied doses of irradiation. Using image analysis in combination with comet assay may be a very useful tool for quantification of absorbed doses for local market checks and also in imported irradiated fish for official control at customs.